The Effects Of Screencasting On Students’ Achievement And Attitude Towards C++ Computer Programming - Cheah, Chin Soon (2018)
The purpose of this study was to design, develop and evaluate the effectiveness of screencast in the learning of C++ Computer Programming among undergraduates. The study also investigated the effects of modality and redundancy principles on the achievement and attitude of the different levels of logic among the undergraduates. The study was conducted based on true experimental pretest and posttest 2 x 2 between subject factorial design. The independent variable consists of the two learning modes namely, screencast and narration mode (SN), and screencast, text and narration mode (STN), while the dependent variables are the achievement test (C++ Computer Programming test) and computer attitude scale (CAS) score.